2004
DOI: 10.1002/ijc.20294
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxins, a novel protein family in lung cancer

Abstract: Cigarette smoke, the major risk factor for lung cancer, induces an accumulation of reactive oxygen species. These have multiple effects on cell defense, cell proliferation and cell death. Thus, compounds involved in the regulators of redox balance can be hypothesized to play a fundamental role in both carcinogenesis and tumor progression. Here, we have evaluated the expressions of all 6 peroxiredoxins (Prxs I-VI) in lung carcinomas. Prxs represent a protein family with the capability of breaking down hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
126
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(131 citation statements)
references
References 35 publications
4
126
1
Order By: Relevance
“…In primary bladder cancer, the PRDX1 and 6 expression levels were significantly elevated in non-progressed cases compared to the progressed cases (34). The overexpression of PRDX was also reported in human breast and lung cancer (16,35). In OSCC, Yanagawa et al studied PRDX1 expression for the first time and found low PRDX1expression levels to be associated with larger tumor masses, lymph node metastases and poorly-differentiated tumors (36).…”
Section: Discussionmentioning
confidence: 92%
“…In primary bladder cancer, the PRDX1 and 6 expression levels were significantly elevated in non-progressed cases compared to the progressed cases (34). The overexpression of PRDX was also reported in human breast and lung cancer (16,35). In OSCC, Yanagawa et al studied PRDX1 expression for the first time and found low PRDX1expression levels to be associated with larger tumor masses, lymph node metastases and poorly-differentiated tumors (36).…”
Section: Discussionmentioning
confidence: 92%
“…20 In addition, strong expression of Prdx6 was observed in affected tissues of patients suffering from various diseases, including psoriasis, 19 sporadic JakobCreutzfeld disease, 45 Parkinson's disease, 46 Pick disease, 47 and cancer. 48 All these conditions are associated with enhanced levels of ROS. 49,50 Thus, the strong expression of Prdx6 in these diseases may be a mechanism to limit the severity of the condition.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, analyses of patient samples have revealed a significant association between PRDX6 expression in breast cancer cells and lymph node metastasis (26). It was similarly reported that PRDX6 expression in lung cancer cells was significantly associated with high-grade dysplasia and tumor progression (23,29). Although these observations suggest that PRDX6 has the ability to support invasiveness and metastasis of the cancer cells analyzed, it is currently unclear whether such functions of PRDX6 depend on its enzymatic activities, although such information is essential for a better understanding of the mechanism of PRDX6 action in cancer cells.…”
Section: Introductionmentioning
confidence: 96%
“…Firstly, PRDX6 is often upregulated in malignant tissues of various human organs, including lung (23,24) and breast (25,26). Moreover, functional studies using analyses of RNA interference and overexpression suggest that PRDX6 does not simply act as a cytoprotective antioxidant enzyme but also supports the growth, invasiveness, and metastasis of breast cancer cells (27).…”
Section: Introductionmentioning
confidence: 99%